(untitled) (Jurnal Bina Praja, 2021)
Identical collaborative governance is used in government and must handle COVID-19 to create fast, precise, focused, integrated and synergistic steps between ministries/agencies, local governments, and other stakeholders. This research describes collaborative governance in efforts to deal with COVID-19 in Riau Province, especially Pekanbaru City, considering that the city recorded a relatively high initial increase in cases compared to other areas in Riau Province as well as the implementation of collaborative management. The research method is qualitative, with the type of research used is the exploratory type and literature study. This article analyses several aspects of collaborative governance, namely the initial role of the government, non-state actors, joint decision making, formal organizing, gaining consensus, and the existence of problems to collaborate both on public policies and services.